Determinants of Employment Growth at MNEs : Evidence from Egypt, India, South Africa and Vietnam - Sumon Kumar Bhaumik; Saul Estrin; Klaus Meyer (Institute for the Study of Labor (IZA), 2004)
Foreign investors are expected to contribute to economic development through a variety of channels. However, many foreign investment operations are small, and almost insignificant in their impact on the local environment. An important indication of the potential contribution of foreign investors is thus their employment growth. Employees working for, and trained by, a multinational enterprise may become carriers of new technology and business practices. The more employees receive access to new knowledge, the more they in turn may spread the knowledge across the economy, for instance by setting up their own businesses. In this paper, we make a first step in investigating the determinants of this important mediating variable, employment growth. For a dataset covering four diverse emerging economies, we find that wholly-owned FDI operations have higher employment growth, while local industry characteristics moderate the growth effect.
Keywords: O13; J21; O33; F23; 330; MNE; employment growth; control; institutions; FDI policy; Multinationales Unternehmen; Direktinvestition; Beschäftigungseffekt; Schätzung; Ägypten; Indien; Südafrika; Vietnam